Registration of Transfer Grant of Rights to Land According to Customary Law as Well as The Role of The Notary / PPAT in Wonossalam, Demak - Rini Setyowati Abadi; Ervin Faizal Nurdiansyah; Achmad Sulchan (Jurnal Akta, 2018)
The transition of land rights for the grant must be conducted through the procedures in accordance with the provisions occured for the transition of land rights for the grant must be registered at the land office to obtain legal certainty in the form of a certificate, so that the land status would be clear. In practice, in the district Wonossalam-Demak are still many people who do grant without going through legal procedures that have been set and raises difficulties on many fronts for legal certainty on the grant agreement. This study aims to determine and analyze the role of notaries in the implementation of transitional registration of land rights because the grant. Notary entitled to be responsible if something happens on the issue of the agreement for him, the responsibility it be liable in peridana, civil, code of conduct, and administration.Keywords: Registration, Transfer of Rights To Land, Customary Law.